Neonatal Immune Adaptation of the Gut and Its Role during Infections - Emilie Tourneur; Cecilia Chassin (Clinical and Developmental Immunology)
The intestinal tract is engaged in a relationship with a dense and complex microbial ecosystem, the microbiota. The establishment of this symbiosis is essential for host physiology, metabolism, and immune homeostasis. Because newborns are essentially sterile, the first exposure to microorganisms and environmental endotoxins during the neonatal period is followed by a crucial sequence of active events leading to immune tolerance and homeostasis. Contact with potent immunostimulatory molecules starts immediately at birth, and the discrimination between commensal bacteria and invading pathogens is essential to avoid an inappropriate immune stimulation and/or host infection. The dysregulation of these tight interactions between host and microbiota can be responsible for important health disorders, including inflammation and sepsis. This review summarizes the molecular events leading to the establishment of postnatal immune tolerance and how pathogens can avoid host immunity and induce neonatal infections and sepsis.